Here in the real world - Pennypacker, Sara, 1951- (Balzer + Bray, an imprint of HarperCollinsPublishers, 2020)
Immersing himself in a fantasy world of knights and chivalry, introverted Ware is sent to a summer camp designed around social interactions and begins building a castle-like private space while clashing with a fellow misfit.